Role of strain echocardiography in patients with hypertension - Oh, Jin Kyung; Park, Jae-Hyeong (Clinical hypertension, 2022)
Hypertension is a well-recognized risk factor for the development of cardiovascular disease, and the early detection of cardiac changes from hypertension can allow reversing these. Hypertensive heart diseases (HHD) refer to the complex and diverse change of the cardiac structure and function secondary to hypertension. Although conventional echocardiography is the most common imaging modality in detecting HHD, it cannot detect subtle changes of cardiac structure in subclinical states. Because strain echocardiography is another echocardiographic modality can detect subclinical myocardial dysfunction by measuring intrinsic myocardial deformation, it became more and more popular in clinical and research fields. In this review article, we described the basic concept of strain echocardiography and summarized several clinical studies showing its clinical utilities in the detection of HHD.